(untitled) (Research, Society and Development, 2021)
The virtual games enable interest and participation of the student, as well as can enable attention, creativity, motor coordination, concentration, among other advantages. The objective of this research was to understand the perceptions of high school teachers in a school in the municipality of Camocim-CE regarding the use and applicability of games in times of pandemic. This is a qualitative, exploratory research, carried out in a high school, located in the municipality of Camocim-CE, whose subjects were chemistry teachers. As a data collection technique, we used the questionnaire, which due to care for the COVID-19 pandemic, was applied remotely, through a message application. With the collected data we could perceive progressive and traditionalist teachers, and that the use of virtual games for some was of paramount importance for the teaching of chemistry contents. We infer the educational virtual games, proved to be efficient and necessary, especially given the reality that we are experiencing with the COVID-19 pandemic.